The development of the maritime sector in Malaysia - Hanizah Idris; Tan, Wan Hin (IOES monograph series, 2010)
This book represents the views of experts in various fields, notably fishery, port and shipping, marine resources and maritime strategic issues. It is hope that this book will serve as material to scholars and researchers interested in the maritime issues in Malaysia exclusively.